The effect of the process conditions and lubricant application on the quality of yarns produced by mechanical recycling of denim-like fabrics - Liu Zewen; Cano Francesc; Ardanuy Mònica (AUTEX Research Journal)
Mechanical textile recycling has great advantages over other types such as chemical or thermomechanical recycling. The main drawback of this textile-to-textile recycling technology is that the length of the fibres is reduced over successive recycling processes. In most cases, due to the length reduction, it is necessary to blend the recovered fibres with virgin fibres to obtain high-quality yarns that can be reincorporated into the textile value chain. Despite the maturity of the technology, this problem has yet to be fully resolved, and it continues to present a major technological challenge. This study aims to determine the optimum shredding conditions to recycle denim-like fabrics with an edge-trim opener machine. It also examines the effect of oiling pre-treatment on the retention of fibre length of the recovered fibres and the performance of yarns produced with the recycled fibres. The best results are achieved by processing the material in three shredding cycles at feeding and opening speeds of 0.3 m/min and 947 rpm, respectively. The addition of lubricant, although not having a significant effect on the efficiency of the defibration process, led to an improvement in the quality of the recycled yarn.